Air Bacteriology of Operation Theatres and Intensive Care Units from a Tertiary Care Hospital in New Delhi - Pritikumari, Patel; Malhotra, Shalini; Garg, Saloni; Yadav, Renu; Bhatia, NK; Duggal, Nandini (International Journal of Innovative Research in Medical Science, 2019)
Background: Hospital-associated infections are a major cause of patient morbidity and mortality. Microbiological contamination of air in the operation theaters (OTs) and Intensive care units (ICUs) is a major risk factor for surgical site and other hospital-associated infections. The aim of the study was to determine the microbial contamination of air in the OTs and ICUs of a tertiary care hospital in north India. Methods: The study was conducted in the department of microbiology, Dr. RML hospital & PGIMER, New Delhi. Air samples were collected from 9 OTs and 4 ICUs by settle plate method between January 2017–June 2018. Bacterial species were isolated and identified by conventional methods. Results: A total of 630 samples were collected from environment of various OTs and ICUs. Out of these, 130 (20%) plates showed bacterial growth and yielded 380 isolates. Emergency OT and ECS OT showed highest bacterial CFU per plate. The most common isolate was Bacillus species 472 (75%) followed by micrococcus 352(56%), Staphylococcus aureus 6 (1%). Conclusion: Routine surveillance of OT and ICU air in conventional OTs where there is no control on air quality, meticulous cleaning and strict adherence to OT and ICU protocol are essential steps for the prevention of hospital acquired infections. Further, the hospitals need to develop and implement processes for good infection control practices